Efeito do ultra-som na atividade de enzimas amilolíticas e sobre a eficiência de hidrólise de amido de mandioca - Leães, Eloisa Xavier (2012)
Ethanol production from cassava undergoes two-stage hydrolysis and fermentation. The starch hydrolysis may be made of acidic or enzymatic way, the latter presents the greatest advantages. In the production of starch hydrolysates by enzymatic conversion enzymes represent a high cost, so the study of new technologies aimed at increasing the efficiency of amylolytic enzymes is of paramount importance to reduce process costs. This study aimed to evaluate the influence of ultrasound on enzymatic hydrolysis of cassava fresh and characterization of the enzymes α-amylase (Liquozyme® SC DS) and glucoamylase (Spirizyme® Fuel) used in the reactions. We determined the temperature and optimum pH, kinetic parameters and thermal stability of enzymes by the hydrolysis of soluble starch, using a water bath and ultrasonic bath. Results showed a small increase in enzyme activities when treated individually during the experiments with ultrasound compared to those made only with the bath under the same conditions of temperature and pH at the time of 30 minutes. The hydrolysis reactions of fresh cassava with both enzymes simultaneously, showed that the use of ultrasound caused a significant increase in the release of total reducing sugars, 24.64 to 64.48% higher compared to the conventional method used in the temperature conditons of 55°C, pH 5.5, and equal amounts of substrate and enzymes. This way the use of ultrasound may reduce the cost of ethanol production using cassava as a carbohydrate source, and a promising technology to be used.